A survey on Fecal Coliform Count, Total Coliform Count and Ammonia concentration using filter drinking water samples collected from restaurants of Shantinagar and Tongi, Dhaka - Shaikat, Mahdi Mubin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2020.